1983
DOI: 10.1161/01.cir.68.5.1136
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of transluminal angioplasty: evidence for formation of aneurysms in experimental atherosclerosis.

Abstract: Quantitative histologic examination (morphometric analysis) of pressure-perfused rabbit atherosclerotic arteries was used to determine whether compression of atheromatous material occurs with transluminal angioplasty. Experimental atherosclerosis was developed in both iliac arteries, with transluminal angioplasty performed on the left iliac while the right iliac served as a nondilated control. Angiography showed equal degrees of luminal narrowing before angioplasty (p = NS). Angioplasty reduced the left iliac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(31 citation statements)
references
References 15 publications
0
30
0
1
Order By: Relevance
“…Morphometric analyses of dilated vessels have verified that angioplasty works primarily through stretching of the vessel with localized aneurysm formation. 8 No evidence for compression of the atheroma could be demonstrated in these studies. In addition, we have shown 9 that acute embolization of lipid or debris does not occur in this model.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Morphometric analyses of dilated vessels have verified that angioplasty works primarily through stretching of the vessel with localized aneurysm formation. 8 No evidence for compression of the atheroma could be demonstrated in these studies. In addition, we have shown 9 that acute embolization of lipid or debris does not occur in this model.…”
Section: Discussionmentioning
confidence: 66%
“…10 " 11 We and others 6 " 8 have previously shown that the rabbit is a suitable model for the study of transluminal angioplasty; the results of the immediate effects show a variety of histopathological findings including dramatic intimal splitting as well as dissection or stretching of the vessel wall. In addition, we have shown that the primary mechanism in angioplasty is stretching of the vessel wall and localized aneurysm formation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The balloon size, ratio of inflated balloon diameter to diameter of adjacent normal artery, total number of balloon inflations, total duration of inflations and post-PTCA incidence of angiographic intimal dissection were not significantly different for the three lesion severity subgroups. A number of studies have demonstrated that the severity of arterial trauma after balloon angioplasty, as judged by the incidence of intimal dissection and acute closure after PTCA (15)(16)(17) or determined histologically after in situ angioplasty (18) or after angioplasty in the cholesterol fed rabbit model (19) is not necessarily related to the severity ofthe lesion being dilated. Severe vessel injury, for example, is often observed after balloon dilatation of moderate lesions (19).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that the severity of arterial trauma after balloon angioplasty, as judged by the incidence of intimal dissection and acute closure after PTCA (15)(16)(17) or determined histologically after in situ angioplasty (18) or after angioplasty in the cholesterol fed rabbit model (19) is not necessarily related to the severity ofthe lesion being dilated. Severe vessel injury, for example, is often observed after balloon dilatation of moderate lesions (19). If, despite the above considerations, one assumes that there was substantially greater injury and platelet deposition in the more severely narrowed segments, one would expect to see an association between lesion severity and (platelet-mediated) vasoconstriction in the dilated segment paralleling the changes seen in the distal segment.…”
Section: Discussionmentioning
confidence: 99%